CLMV collaborations with Malaysia, towards sustaining asian identities in Higher Education an interview with the Vice Rector of Cantho University, Vietnam, Dr. Do Van Xe. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)

(untitled)
The higher education landscape is changing rapidly.Driven by powerful forces such as economy, geography and technology, higher education has diversified and flourished.Online learning, for instance, is getting more common and cross-border education is becoming more popular. There have also been major changes in perception, demand, funding and governance. With such dramatic changes taking place in higher education contexts the world over, there has been rising concern for strengthening higher education in the Asia Pacific region.